3‐Hz subthreshold oscillations of CA2 neurons In vivo. Issue 12 (27th September 2016) - Matsumoto, Nobuyoshi; Okamoto, Kazuki; Takagi, Yuki; Ikegaya, Yuji
ABSTRACT: The CA2 region is unique in the hippocampus; it receives direct synaptic innervations from several hypothalamic nuclei and expresses various receptors of neuromodulators, including adenosine, vasopressin, and oxytocin. Furthermore, the CA2 region may have distinct brain functions, such as the control of instinctive and social behaviors; however, little is known about the dynamics of the subthreshold membrane potentials of CA2 neurons in vivo . We conducted whole‐cell current‐clamp recordings from CA2 pyramidal cells in urethane‐anesthetized mice and monitored the intrinsic fluctuations in their membrane potentials. The CA2 pyramidal cells emitted spontaneous action potentials at mean firing rates of ∼0.8 Hz. In approximately half of the neurons, the subthreshold membrane potential oscillated at ∼3 Hz. In two neurons, we obtained simultaneous recordings of local field potentials from the CA1 stratum radiatum and demonstrated that the 3‐Hz oscillations of CA2 neurons were not correlated with CA1 field potentials. In tetrodotoxin‐perfused acute hippocampal slices, the membrane potentials of CA2 pyramidal cells were not preferentially entrained to 3‐Hz sinusoidal current inputs, which suggest that intracellular 3‐Hz oscillations reflect the neuronal dynamics of the surrounding networks. © 2016 Wiley Periodicals, Inc.